The factors influencing customer satisfaction towards the tour service provided in Rumah Terbalik, Tamparuli / Casey Brent Bagah - Bagah, Casey Brent (2014)
The tourism sector is constantly growing from time-to-time. Satisfaction is essentially the most important factor in the tourism industry. For guided tours, customers can be influenced by various factors which enhance their satisfaction of the tour. This study attempts to examine the satisfaction of customers towards the tour service provided in Rumah Terbalik. Tamparuli, which is one of the popular attractions in Sabah, Malaysia. However, the factors influencing customer satisfaction have yet to be indentified. Several factors were selected and examined to find whether it is related to customer sat isfaction. These factors include tour motivation, tour expectation and tour guide. The analysis showed that customers did come back again to visit Rumah Terbalik. Therefore, this research aims to identify the factors influencing customer satisfaction towards the tour service provided in Rumah Terbalik, Tamparuli. The relationship of the influencing factors and customer satisfaction were also studied.